ADHD TREATMENT: FROM MEDICATION TO BEHAVIORAL THERAPIES- A SYSTEMATIC REVIEW - Barbara Madoń; Agnieszka Brzezińska; Maciej Dudziński; Wojciech Gąska; Izabela Lekan; Michał Lenart; Joanna Mazurek; Ignacy Rożek; Barbara Teresińska; Weronika Tuszyńska (International Journal of Innovative Technologies in Social Science, 2025)
Introduction: Nowadays, ADHD is one of the most common diagnoses in the mental health field. It presents a wide spectrum of clinical presentations that affect patients’ everyday life. Variety of symptoms make each patients’ needs individual, and because of that, treatment of ADHD must be adjusted to each person separately to achieve the best possible outcome.Materials and methods: This article, based on a PubMed review of available research, examines ADHD treatmentKey findings and conclusions: Options in first line medications are limited, therefore formulation technologies are one of the few methods to modify the therapy. Alternative to that, especially for patients that cannot take stimulants, are non-stimulant medications generally used in other medical fields. Additionally, psychotherapy is inherent for patients to understand their disorder, which allows them to accept it. The aim of this article is to present the basis of a complex issue, as ADHD treatment is.